2019
DOI: 10.1111/1750-3841.14808
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Visual Cues on Consumer Expectation, Emotion and Wellness Responses, and Purchase Intent of Red Chili Powders

Abstract: The effects of visual cues on familiarity, expected heat intensity, liking of appearance, emotional and wellness responses, and purchase intent (PI) before and after disclosing information associated with red chili powders were determined using a 3‐point scale, a 15‐cm line scale, a 9‐point hedonic scale, a 15‐cm line scale, and a binomial scale, respectively. In this study, consumers only visually evaluated red chili powder samples without sniffing nor tasting. Eight chili powders were prepared according to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The observed differences in expected emotional profiles elicited by P‐cp, P‐mp and P‐cp*mp may be explained by the disconfirmation of the expected colours of the fermented rice noodle products. Consumers expect the colour of food depending on their prior experience and product familiarity (Maina, 2018; Ngoenchai et al ., 2019; Chonpracha et al ., 2020). The more familiar a product is, the more specific expectations by consumers; therefore, if there is a discrepancy between their expectations and perceived product characteristics, it disconfirms their intentions (Schiebler, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The observed differences in expected emotional profiles elicited by P‐cp, P‐mp and P‐cp*mp may be explained by the disconfirmation of the expected colours of the fermented rice noodle products. Consumers expect the colour of food depending on their prior experience and product familiarity (Maina, 2018; Ngoenchai et al ., 2019; Chonpracha et al ., 2020). The more familiar a product is, the more specific expectations by consumers; therefore, if there is a discrepancy between their expectations and perceived product characteristics, it disconfirms their intentions (Schiebler, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Both rating and RATA scores (when treated as a continuous outcome) were analyzed using ANOVA to determine the emotion and wellness terms with significant differences among the five herbal drinks. Next, the significant terms were analyzed using DMRT for multiple comparisons [28]. Principal component analysis (PCA) was performed to identify the emotion and wellness terms that contributed to overall differences among the herbal drinks and to classify the products based on emotion and wellness responses.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in the field of sensory and consumer science, the evaluation of the emotional response to food and beverage is a critical factor that affects a person's food choice and also can indicate the emotional experiences while consuming food (Kanjanakorn and Lee, 2017). Ngoenchai et al (2019) reported that the emotional responses to visual appearance cues (e.g. written information, images, logos and product names) play an essential role in adding value and affecting expectations and emotional responses.…”
Section: Introductionmentioning
confidence: 99%